SGS-LTER 2003 soil water supplemental proposal - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 2003)
A request for funds to install soil moisture probes at five sites across a research site.
Monitoring and modeling soil water dynamics on shortgrass steppe
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: shortgrass steppe; long term ecological research; grassland ecology; Pawnee National Grassland; Central Plains Experimental Range